Estimation the Saturation Flow Rate at Far-side and Nearside Legs of Signalized Intersections – Case Study: Rasht City. (2016) - Bargegol, Iraj; Amlashi, Afsaneh Tahriri; Gilani, Vahid Najafi Moghaddam
Abstract: Saturation flow rate as one of the important characteristics of traffic flow plays a key role to determine the capacity and delay in signalized intersections. So far, various studies have been done to evaluate the saturation flow rate at nearside legs of intersections which is fit to geometrical dimensions, traffic flow characteristics and the behaviour of the drivers. However, despite the deference between the above specifications, no study has been conducted on the saturation flow rate at far-side legs and considering the difference between the saturation flow rate at nearside and far-side legs in case of reducing the number of lanes, lane width and other effective factors, it seems to be necessary to determine the saturation flow rate at far-side legs. In the present study, using field data collection at five signalized intersections in Rasht city, the saturation flow rate is estimated and analyzed by macroscopic and microscopic methods, considering the existing lane width at nearside and far-side legs of the intersections. The results indicate that the values of saturation flow rate at far-side legs using the microscopic method are higher than the similar values in nearside legs. Also there is a primarily linear relationship (R 2 =0.957) between the lane width and saturation flow rate at far-side legs using the macroscopic method. There is an exponential non-linear relationship at far-side legs (R 2 =0.859) and a logarithmic non-linear relationship at nearside legs (R 2 =0.105) between the lane width and saturation flow rate using the microscopic method. In regard to far-side leg's R 2, it seems that the main criterion in determining the saturation flow rate is the lane width, while at nearside leg more effective parameters need to be used to determine the values of saturation flow rate.